Co-Occurrence of Rarest Type of Dysphagia Lusoria (Type N-1) and Eosinophilic Esophagitis in a Cognitively Disabled Individual - Kishore Kumar; Jasbir Makker; Hassan Tariq; Ariyo Ihimoyan; Chime Chukwunonso; Masooma Niazi; Michael Lombino; Muhammad Kamal; Harish K. Patel (Case Reports in Medicine)
Dysphagia is an expressive symptom, described by an individual as “difficulty in swallowing.” Dysphagia due to esophageal compression from an aberrant right subclavian artery is rare, and it is termed as “dysphagia lusoria.” We present a rare case of co-occurrence of dysphagia lusoria with esophageal eosinophilia in a patient with cognitive disability which portends a case with diagnostic challenge and treatment dilemma. A 31-year-old man with intellectual disability, cerebral palsy, previous history of feeding difficulty, and esophageal food impaction presented with esophageal foreign body impaction. He has no known history of atopy and food allergies. There was no laboratory evidence of peripheral eosinophilia. The IgE-mediated allergic test was unremarkable. His prior presentation revealed a diagnosis of eosinophilic esophagitis. The imaging studies showed proximal esophageal dilatation with extrinsic compression at the level of the upper esophagus. The foreign bodies were removed successfully through the help of upper endoscopy. Subsequent evaluation revealed a rare type of dysphagia lusoria (type N-1) due to an aberrant left subclavian artery arising from the right-sided aortic arch. The patient’s family refused further management of artery lusoria. Prolonged stasis of secretions and food in the esophagus can also lead to increased esophageal eosinophils. In our case, it remains undetermined whether increased number of esophageal eosinophils resulted from primary eosinophilic esophagitis or due to prolonged food stasis from esophageal compression caused by an aberrant subclavian artery. However, food impaction right above the compression site makes dysphagia lusoria the likely etiology.